INTEGRASI STEAM-PjBL PADA PEMBELAJARAN IPA DI SMP NEGERI 3 KARANGMOJO, BANTUL–YOGYAKARTA: PROYEK MIKROSKOP SEDERHANA - Supriyatin, Supriyatin; Rahayu, Sri; Suhadi, Anggi Putri; Simarmata, Remli Nelmian (Jurnal Terapan Abdimas, 2023)
Abstract. Many teachers still have not integrated STEAM-PjBL in learning. Students who are accustomed to conventional learning and have never operated a microscope as a tool in understanding science material. STEAM-PjBL learning is the right solution in facilitating and providing space for students to be able to overcome these problems, STEAM-PjBL is also a place to hone students' abilities and skills to face the demands of the current modernization era. The purpose of this activity is to introduce, implement and integrate STEAM-PjBL in science learning. The population in this activity is all 8th grade students of SMP 3 Karangmojo and the subject of the activity is class 8 B with a total of 30 people. The activity will be held on July 15, 2022. The stages of STEAM-PjBL integration consist of Reflection, Research, Discovery, Application and communication. The activities that have been carried out have given positive results, 80% of students "strongly agree" that learning science with the STEAM-PjBL model on the "simple microscope" project is interesting, fun, fosters enthusiasm, gives its own satisfaction in learning, makes it easier for students to understand the material and demands participation active studentsAbstrak. Banyak guru yang masih belum mengintegrasikan STEAM-PjBL dalam pembelajaran. Siswa yang terbiasa dengan pembelajaran konvensional dan belum pernah mengoperasikan mikroskop sebagai salah satu alat dalam memahami materi IPA. Pembelajaran STEAM-PjBL merupakan solusi tepat dalam memfasilitasi dan memberikan ruang kepada siswa untuk dapat mengatasi masalah tersebut, STEAM-PjBL juga menjadi wadah dalam mengasah kemampuan dan keterampilan siswa untuk menghadapi tuntutan era modernisasi saat ini. Tujuan dari kegiatan ini adalah untuk mengenalkan, menerapkan dan mengintegrasikan STEAM-PjBL pada pembelajaran IPA.  Populasi pada kegiatan ini adalah seluruh siswa kelas 8 SMP 3 Karangmojo dan subjek kegiatannya adalah kelas 8 B dengan jumlah 30 orang. Kegiatan dilaksanakan pada 15 juli 2022. Tahapan integrasi STEAM-PjBL terdiri atas Reflection, Research, Discovery, Application dan communication. Kegiatan yang telah dilakukan memberikan hasil yang positif, 80% siswa “sangat setuju” bahwa pembelajaran IPA dengan model STEAM-PjBL pada proyek “mikroskop sederhana” menarik, menyenangkan, menumbuhkan semangat, memberikan kepuasan tersendiri dalam belajar, mempermudah siswa memahami materi dan menuntut partisipasi aktif siswa.